1963
DOI: 10.1017/s0031182000073923
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the free-living stages of the stomach worm Haemonchus contortus

Abstract: Outdoor observations were made on the rate of development of the free-living stages of H. contortus at different times of the year, and on the migratory activities and longevity of the larvae in faeces, on herbage and in soil.The effects of temperature and humidity on the survival and development of eggs and larvae, both in faeces and when separated from the faeces, were studied in the laboratory.The results of these observations are discussed in relation to the heavy mortality of the free-living stages of H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

1974
1974
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 9 publications
6
32
0
1
Order By: Relevance
“…Clunies Ross (1932) appears to have been the first to recognise the distinction between resistance to infection, in terms of parasite numbers, and resistance to the impact of infection, in terms of host disease. Although Clunies Ross did not use the term, later studies described the latter phenomenon as disease resilience (Albers et al 1987;Bisset and Morris 1996;Bishop 2012;Doeschl-Wilson and Lough 2014), which is typically defined in terms such as a capacity to maintain high productivity in the face of ongoing infection (Bisset and Morris 1996;Bishop 2012).…”
Section: Historical Concepts Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Clunies Ross (1932) appears to have been the first to recognise the distinction between resistance to infection, in terms of parasite numbers, and resistance to the impact of infection, in terms of host disease. Although Clunies Ross did not use the term, later studies described the latter phenomenon as disease resilience (Albers et al 1987;Bisset and Morris 1996;Bishop 2012;Doeschl-Wilson and Lough 2014), which is typically defined in terms such as a capacity to maintain high productivity in the face of ongoing infection (Bisset and Morris 1996;Bishop 2012).…”
Section: Historical Concepts Of Resiliencementioning
confidence: 99%
“…Although factors influencing the development of phenotype have been a focus of research for over a century (Strandberg 2009), the past decade has seen a substantial increase in interest in resilience and robustness of animals to environmental effects Hermesch and Dominik 2014). Resilience to the effects of parasitic disease in farm animals was first recognised 80 years ago by Clunies Ross (1932), yet, in recent years, a broader concept of resilience has emerged in animal and human sciences that encompasses not only the response of the individual to disease challenges but also the individual's response to environmental and social stressors (Russo et al 2012;Wu et al 2013;Hermesch and Dominik 2014). Therefore, in Section 2 of this review, we examine the biological processes whereby animals respond to signals from their internal and external environments, the influence of personality, emotion and cognitive functions of the animal on these responses, how responses to stimuli are regulated and what happens when signals are noxious or overtax the capacity of the animal to cope.…”
Section: Introductionmentioning
confidence: 99%
“…N. battus, T. circumcincta and Trichostrongylus spp. appear to tolerate much lower temperatures very well (Andersen et al, 1966;Andersen and Levine, 1968;Ash and Atkinson, 1986;Pandey et al, 1993), whereas H. contortus appears sensitive to temperature drops below 238C (Rose, 1963;Todd et al, 1976;Philip, 1983). Overwinter survival rates of the latter species may, therefore, be enhanced if fewer 'extreme' frost events take place.…”
Section: Predicted Climatic Effects On Parasite Ecologymentioning
confidence: 99%
“…Investigations carried out by Shorb (1944) and Dinaburg (1944) in Australia, by Dinnik (1958, 1961) in the Kenya Highlands, by Silverman and Campbell (1959) in Scotland, by Rose (1963) in England and by Altaif and Yakoob (1987) in Iraq on the development and survival of Haemonchus contomts showed that the rate of development and the longevity of the eggs varied at different temperatures and humidity and in different parts of the world. H. contortus is the main cause of hehninthosis in sheep in the Plateau State of Nigeria and it is the most common strongyle found in most of the sheep brought for post morfem examination at the National Veterinary Research Institute in Vom.…”
Section: Introductionmentioning
confidence: 99%